Presisi Bahasa dalam Direktori Putusan: Telaah Kesalahan Ejaan dan Diksi Pada Konsideran Tingkat Pertama dan Kasasi Mahkamah Agung - Dali, Meilina Widya; Baruadi, Agustina; Gonibala, Meilan; Hakim, Siti Rania Khumairah; Hasan, Sholeha; Laparaga, Nabila Putri; Rauf, Mohamad Ziad; Nusi, Mohamad Aprianto; Smith, Farhaniyah; Lakadjo, Raihan; Anau, Syabila Raihanah; Djabu, Daniyal Ahyan; Muhammad, Ammar Farrel (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to describe the linguistic precision in the recitals of criminal judgments, particularly those related to spelling and diction errors. The method used is quantitative-descriptive research with documentation techniques. The research data consisted of the recitals of four criminal verdicts, namely two verdicts from the District Court and two cassation verdicts from the Supreme Court, which were obtained through the Directory of Verdicts of the Supreme Court of the Republic of Indonesia. The data were analyzed through the stages of identifying language errors, classifying them based on the type of error, and tabulating the frequency to see the trends and comparisons between the levels of verdicts. The results of the study show that language errors are more prevalent in first-level decisions than in cassation decisions. The dominant errors are spelling errors, such as incorrect spelling of standard words and word form errors, while diction errors are found in limited numbers. In addition, the calculation of the error ratio per 1,000 words shows that the linguistic precision of cassation decisions is relatively better than that of first-level decisions. These findings emphasize the importance of linguistic accuracy and the application of standard linguistic rules in the drafting of court decisions.